INTERLEUKIN-18 AND EMPHYSEMA IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Debreshlioska, Angjela; Gjoreska, Milena Miletic; Kostoska, Marija; Kirijas, Meri; Jovanovski, Kristijan (Journal of Morphological Sciences; Vol 8 No 1 (2025): JMS, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive lung disease characterized by persistent respiratory symptoms and airflow limitation due to airway and/or alveolar abnormalities usually caused by significant exposure to noxious particles or gases. Emphysema involves the destruction of alveolar walls, resulting in diminished gas exchange and airflow constraint. Interleukin-18 (IL-18), a potent pro-inflammatory cytokine, plays a pivotal role in the immune response and inflammation regulation, implicated in various autoimmune and inflammatory diseases. Elevated IL-18 levels have been noted in emphysema patients, contributing to chronic inflammation, tissue damage, and airway remodeling. Aim: The aim of this study was to determine IL-18 values in patients with emphysema, compare their values in patients with different stages of the disease, and analyze their correlation with inflammatory and clinical parameters. Materials and Methods: This cross-sectional study was conducted at the University Hospital of Pulmonology and Allergology in Skopje, involving 30 COPD patients, randomly sampled, meeting specified inclusion and exclusion criteria. Signed informed consent was obtained from all participants. Data on demographic, clinical, and smoking history were obtained from medical records. Spirometry and imaging techniques were performed for lung function and emphysema assessment. Blood samples were collected for inflammatory parameters measurement and IL-18 concentration measurement using Luminex technology. The study included 30 COPD patients (10 women, 20 men), with an average age of 65.2 years, all of whom were smokers. Emphysema was present in 26 patients (86.5%): 11 with mild, 10 with moderate, and 5 with severe emphysema. Average age increased with severity: 52.3 years (no emphysema), 61.5 (mild), 66.4 (moderate), and 65.6 (severe). Cough prevalence was 75% (no emphysema) to 81.2% (mild) and 80% (moderate and severe). Dyspnea rose from 50% (no emphysema) to 100% (severe). Chest pain occurred in 80% of severe cases. FEV1 values decreased with severity: 64.5% (no emphysema), 60.3% (mild), 47.5% (moderate), and 37.2% (severe). Inflammatory parameters (leukocyte and neutrophil counts) did not vary by emphysema severity, but IL-18 levels significantly correlated with severity. In correlation analysis, higher IL-18 levels were associated with emphysema severity and decline in lung function (FEV1), while no significant correlations were found between IL-18 and age, chest pain, dyspnea, cough, or leukocyte counts. These findings highlight the potential utility of IL-18 as a biomarker in emphysema management and emphasize the need for further research to elucidate its therapeutic implications. Keywords: COPD, emphysema, Interleukin–18.